2020
DOI: 10.1186/s12891-020-03824-y
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment strategy for atypical ulnar fracture due to severely suppressed bone turnover caused by long-term bisphosphonate therapy: a case report and literature review

Abstract: Background Atypical fractures may occur due to the combined effect of severely suppressed bone turnover (SSBT) caused by long-term bisphosphonate treatment and chronic repetitive bone microdamage. Atypical fracture of the ulna due to SSBT is a rare entity; there is no standardized treatment strategy for this condition. We successfully treated a patient with atypical fracture of the ulna. Herein, we present this patient, review the relevant literature, and discuss the treatment strategy. Case presentation An 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Moreover, Tsuchie et al reported that the administration of teriparatide after the occurrence of the first AFF and the use of active vitamin D3 after the completion of teriparatide therapy may prevent the recurrence of AFF [ 18 ]. Concerning the non-weight-bearing bones, Abe et al reviewed the reported cases of AUFs and described the difficulty in the treatment of AUFs as has been encountered with AFFs [ 13 ]. In the cases of the two reported patients and the present patient with atypical scapular fracture, BMA treatment was discontinued and the patients were treated conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tsuchie et al reported that the administration of teriparatide after the occurrence of the first AFF and the use of active vitamin D3 after the completion of teriparatide therapy may prevent the recurrence of AFF [ 18 ]. Concerning the non-weight-bearing bones, Abe et al reviewed the reported cases of AUFs and described the difficulty in the treatment of AUFs as has been encountered with AFFs [ 13 ]. In the cases of the two reported patients and the present patient with atypical scapular fracture, BMA treatment was discontinued and the patients were treated conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of the Russell-Taylor classification system for subtrochanteric fractures exemplifies this trend, providing a framework that informs surgical planning and implant selection (17). The management of atypical fractures, particularly those associated with long-term bisphosphonate therapy, further illustrates the complexity of treatment strategies, necessitating vigilant monitoring and, in some cases, prophylactic fixation to prevent complication progression (18). The management of proximal femur fractures requires a multifaceted approach that integrates the latest advances in surgical techniques, a deep understanding of bone biomechanics, and a personalized treatment strategy that considers the unique characteristics of each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in recent years, there have been increasing incidence of atypical ulnar fractures (AUFs) in addition to AFFs caused by SSBT (7,8). AUF treatment is difficult, and many authors have reported that bone union is not achieved (9,10). Therefore, the discontinuation of bone resorption inhibitors, as well as the use of bone grafting, dual plate fixation, low-intensity pulsed ultrasound (LIPUS), and teriparatide are recommended (9,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…AUF treatment is difficult, and many authors have reported that bone union is not achieved (9,10). Therefore, the discontinuation of bone resorption inhibitors, as well as the use of bone grafting, dual plate fixation, low-intensity pulsed ultrasound (LIPUS), and teriparatide are recommended (9,11,12). However, discontinuation of bone-resorbing drugs is problematic in patients with bone metastases, and AUFs treatment in such patients has been reported to be challenging (11).…”
Section: Introductionmentioning
confidence: 99%